1987
DOI: 10.1007/bf00292537
|View full text |Cite
|
Sign up to set email alerts
|

The complement system in Type 1 (insulin-dependent) diabetes

Abstract: The complement proteins C1q, r, s, C2, C4, C3, factor B, C5, C6, and the inhibitors, C1 inhibitors, factors I and H were measured in 35 patients with recently diagnosed Type 1 (insulin-dependent) diabetes, 76 patients with longer-duration disease (30 with complications) and 43 first-degree healthy relatives. We found that C1q, C4 and C3 were reduced significantly in all groups of patients (p less than 0.001 for each protein in recent onset and uncomplicated patients; p less than 0.01, p less than 0.01 and p le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
14
0
1

Year Published

1987
1987
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 28 publications
5
14
0
1
Order By: Relevance
“…This is consistent with previous work showing that improved glycaemic control in diabetes is associated with reduction in inflammatory markers [27]. Studies on C3 levels in autoimmune diabetes showed contradictory results ranging from elevated C3 [28,29], to normal or reduced levels [30]. In the current study, samples were collected from individuals who had the condition for longer than 5 years, minimising the risk of an active autoimmune process interfering with C3 levels.…”
Section: Discussionsupporting
confidence: 88%
“…This is consistent with previous work showing that improved glycaemic control in diabetes is associated with reduction in inflammatory markers [27]. Studies on C3 levels in autoimmune diabetes showed contradictory results ranging from elevated C3 [28,29], to normal or reduced levels [30]. In the current study, samples were collected from individuals who had the condition for longer than 5 years, minimising the risk of an active autoimmune process interfering with C3 levels.…”
Section: Discussionsupporting
confidence: 88%
“…Presumably this rapid plasma disappearance reflects the multifunctional nature of vitronectin with its capacity to be activated by a number of agents to form multimolecular complexes. In comparison with results obtained previously for other human complement proteins in rabbits such as C3 (T 1=2 , 35-40 h [26] ), and C9 (T 1=2 , 20 . 6-29 .…”
Section: Discussionsupporting
confidence: 67%
“…A native but spontaneously multimerized 125 I-labelled preparation was also rapidly cleared from the circulation, with a concomitant increase in the release of free 125 I, so that the rapid clearance of urea activated vitronectin was not simply a function of its treatment. These and other data [13,26] demonstrate the sensitivity of in vivo metabolic parameters of proteins to their structure. We did not specifically investigate the fate of vitronectin sequestered by organs, but it remains likely that the spleen, lung and liver, or the reticuloendothelial elements therein, are sites of its metabolism.…”
Section: Discussionsupporting
confidence: 52%
“…Charlesworth et al [26] have recently demonstrated in young diabetic patients reduced serum levels of several complement proteins which partially, although not exclusively, depended on the presence of null alleles. This observation and our data which associate C4BQO by itself with young age of onset are in accordance with the hypothesis of a relationship between diminished protection against viruses due to a defective complement mechanism and early-onset diabetes, raised already several years ago [27].…”
Section: Discussionmentioning
confidence: 96%